Fraud Triangle Elements, Financial Distress and Financial Statement Fraud by Transportation Companies in Indonesia - Inayati, Titik; Arochman, Maqbulla; Kholidiah, Kholidiah (Journal of Business Management and Economic Development, 2025)
This research was conducted after the Covid 19 pandemic, when the growth of transportation and logistics companies experienced a very drastic decline due to large-scale social restrictions. After Covid-19, transportation and logistics companies experienced growth of 25.81% in the 2021-2022 period. Several previous incidents related to fraudulent financial reporting in a transportation company raised concerns among investors that fraudulent financial reporting efforts would result in the company's bankruptcy. The Fraud Triangle Theory describes three conditions that cause fraudulent behavior: pressure, opportunity, and rationalization. This type of research uses a quantitative method by looking for the influence of dependent, independent and moderating variables. The population in this study were 31 transportation and logistics companies listed on the Indonesia Stock Exchange in 2020-2022. The nonprobability sampling technique used the purposive sampling technique. The sample was 19 transportation and logistics sector companies listed on the Indonesia Stock Exchange, so that the data processed was 19 companies in 3 years, resulting in 57 samples. The data processing analysis tool used Smart PLS 3.0. The results of the study indicate (1) rationalization does not affect financial statement fraud, (2) pressure does not affect Financial Distress, (3) Opportunity affects Financial Distress, (4) pressure and opportunity do not affect Financial Distress. Statement Fraud is moderated by Financial Distress, (5) Opportunity affects Financial Statement Fraud (6) Financial Distress has no effect on Financial Statement Fraud. This study contributes to investors in making investment decisions and developing the science of Financial Management, related to financial distress, the fraud triangles theory and financial statement fraud.